A novel hybrid carbon materials-modified electrochemical sensor used for detection of gallic acid. (January 2022) - Terbouche, Achour; Boulahia, Soumeya; Mecerli, Sarah; Ait-Ramdane-Terbouche, Chafia; Belkhalfa, Hakim; Guerniche, Djamila; Sehailia, Moussa; Bachari, Khaldoun; Mezaoui, Djillali; Hauchard, Didier
Graphical abstract: Highlights: Electrical conductivity measurements were reported for new hybrid carbon materials. Carbon Spheres (CSs)/Activated Carbon (AC)-carbon nanotubes (CNTs) shows highest electrical conductivity. The charge transfer coefficient reveals a better electro-catalytic oxidation mechanism of gallic acid. The cavity microelectrode (CME) modified with CSs/AC-CNTs exhibits a lower LOD of gallic acid. The reproducibility and stability of CME/CSs/AC-CNTs revealed that the RSD % was about 1.44 and 3.7%, respectively. Abstract: Novel hybrid carbon materials such as activated carbon-carbon nanotubes (AC-CNTs) and carbon spheres/activated carbon-carbon nanotubes (CSs/AC-CNTs) based on activated carbon (AC) derived from the pits of Algerian date palm have been prepared and characterized. In addition, the carbon paste electrodes based on graphite carbon (GC) and cavity microelectrode (CME) modified with these hybrid materials were used to detect gallic acid at pH = 7 using square wave voltammetry method (SWV). The conductivity measurements revealed that CSs/AC-CNTs is more conducting than AC-CNTs. SWV measurements showed that the oxidation current was directly proportional to the concentrations of gallic acid (from 0 to 0.00536 M) with the lowest limit of detection (LOD), reaching 6.43 µM and 3.64 µM using GC/CSs/AC-CNTs electrode and CME/GC/CSs/AC-CNTs sensor, respectively. The reproducibility and the stability of the studied sensor were confirmed by the relative standard deviation of the oxidation current response of gallic acid (RSD Reproducibility  = 1.44% and RSD Stability  = 3.7%).